Optimal monetary and fiscal policy: a linear-quadratic approach - Pierpaolo Benigno; Michael Woodford (European Central Bank (ECB), 2004)
We propose an integrated treatment of the problems of optimal monetary and fiscal policy, for an economy in which prices are sticky and the only available sources of government revenue are distorting taxes. Our linear-quadratic approach allows us to nest both conventional analyses of optimal monetary stabilization policy and analyses of optimal tax-smoothing as special cases of our more general framework. We show how a linear-quadratic policy problem can be derived which yields a correct linear approximation to the optimal policy rules from the point of view of the maximization of expected discounted utility in a dynamic stochastic general-equilibrium model. Finally, we derive targeting rules through which the monetary and fiscal authorities may implement the optimal equilibrium.
Keywords: E52; E61; E63; 330; Loss function; output gap; targeting rules; tax smoothing